2018
DOI: 10.4103/0366-6999.227618
|View full text |Cite
|
Sign up to set email alerts
|

Protectin DX Exhibits Protective Effects in Mouse Model of Lipopolysaccharide-Induced Acute Lung Injury

Abstract: Background:Acute lung injury (ALI) is a severe disease with high mortality and poor prognosis. Protectin DX (PDX), a pro-resolving lipid mediator, exhibits protective effects in ALI. Our experiment aimed to explore the effects and related mechanisms of PDX in mice with ALI induced by lipopolysaccharide (LPS).Methods:BALB/c mice were randomly divided into five groups: sham, LPS, LPS plus 1 ng of PDX (LPS + PDX-1 ng), LPS plus 10 ng of PDX (LPS + PDX-10 ng), and LPS plus 100 ng of PDX (LPS + PDX-100 ng). Broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…TNF‐α is a central mediator of inflammation and plays an important role in the host response to injury, but overexpression of TNF‐a can result in severe tissue damage and underlies a number of disease states, such as rheumatoid arthritis, ARDS and malignancy 28,29 . In the present study, we found that PDX could inhibit TNF‐α expression to protect lung tissues, which was consistent with a previous study showing that PDX abolished zymosan‐A‐induced TNF‐α production 30 . We also found that TNF‐α was mainly expressed on recruited macrophages and worked by binding with TNFR, which was expressed on resident macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…TNF‐α is a central mediator of inflammation and plays an important role in the host response to injury, but overexpression of TNF‐a can result in severe tissue damage and underlies a number of disease states, such as rheumatoid arthritis, ARDS and malignancy 28,29 . In the present study, we found that PDX could inhibit TNF‐α expression to protect lung tissues, which was consistent with a previous study showing that PDX abolished zymosan‐A‐induced TNF‐α production 30 . We also found that TNF‐α was mainly expressed on recruited macrophages and worked by binding with TNFR, which was expressed on resident macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…The treated mice also had reduced TNF‐α and neutrophil infiltration into the lungs 83 . Additionally, PDX improved lung histopathology, reduced lung inflammation, and mitigated pulmonary edema in a mouse model of acute lung injury 84 …”
Section: Spms In Inflammatory Lung and Airway Conditions And Injurymentioning
confidence: 92%
“…83 Additionally, PDX improved lung histopathology, reduced lung inflammation, and mitigated pulmonary edema in a mouse model of acute lung injury. 84 While further studies, and particularly clinical studies, are necessary, the preclinical data suggest that SPMs could offer a new therapeutic strategy to decrease the severity and duration of ARDS by improving alveolar fluid clearance and decreasing excessive inflammation.…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…92 Only 1 ng per animal of PDX, an isomer of PD1, can alleviate lipopolysaccharide-induced acute lung injury, inhibiting neutrophil infiltration and reducing pro-inflammatory mediators such as IL-1β, IL-6, TNF-α, and MIP-1α. 93 In acute lung injury, PDX improved the alveolar fluid clearance and decreased edema by upregulating the sodium channel and Na, K-ATPase levels. 94 With respect to acute lung injury, Xia et al 95 described that PDX ameliorates cecal ligation-induced sepsis through the decrease of IL-1β, IL-6, TNF-α, and MCP-1 in BALF, with the consequent decline of neutrophil influx.…”
Section: Specific Pro-resolving Mediators (Spms) In Murine or In Vitr...mentioning
confidence: 99%